Feasibility and Efficacy of an ACT-Based Intervention for Malaysian Parents of Children with Special Health Care Needs: A Pilot Study - Re Gal, Lim; Siok Ping, Voon; Fitri Suraya, Mohamad (Brieflands, 2025)
Background:Parents of children with special health care needs (CSHCN) often experience elevated stress and poorer mental health; yet, parent-focused interventions are frequently overlooked. Objectives:This study evaluated the culturally adapted My-CARE, an Acceptance and Commitment Therapy (ACT)-based protocol, for Chinese Malaysian parents of CSHCN. Methods:Eight parents participated in a pilot study that evaluated the protocol's reliability, feasibility, acceptability, satisfaction, and preliminary efficacy. Parental psychological distress, psychological flexibility (PF) and inflexibility (PI), and parenting stress were measured using the Depression Anxiety Stress Scale-21 (DASS-21), Multidimensional Psychological Flexibility Inventory (MPFI), and Parenting Stress Index (PSI). Results:Results indicated good reliability (Cronbach’s alpha of 0.87), feasibility, acceptability, and satisfaction ratings. The average attendance was 94%. Questionnaire completion rates ranged from 95 to 100%. Satisfaction and acceptability scores averaged 96.73% and 94.17%, respectively. Additionally, participants reported reduced psychological distress, PI, and parenting stress, along with improved PF, with small to large effect sizes (g = 0.08 to 0.98). Notably, depression significantly improved [t (7) = 3.11; P = 0.02; g = 0.98]. Conclusions:These findings support the feasibility and potential efficacy of the ACT-based protocol adapted to the linguistic and cultural contexts of Chinese Malaysian parents of CSHCN. Future studies with larger samples, a control group, and follow-up assessments are needed to validate efficacy.